Glaucoma - M. Ruiz, Pedro Henrique (Revista da Faculdade de Ciências Médicas de Sorocaba, 2006)
Almeida GV. Glaucoma. Rev Fac Ciênc Méd Sorocaba. 2005;7(2). Disponível em: http://revistas.pucsp.br/index.php/RFCMS/article/view/244